Structure and Coding Content of CST (BART) Family RNAs of Epstein-Barr Virus - Smith, Paul R. (American Society for Microbiology, 2000)
CST (BART BARF0) family viral RNAs are expressed in several types of Epstein-Barr virus (EBV) infection, including EBV-associated cancers. Many different spliced forms of these RNAs have been described; here we have clarified the structures of some of the more abundant splicing patterns. We report the first cDNAs representing a full-length CST mRNA from a clone library and further characterize the transcription start. The relative abundance of splicing patterns and genomic analysis of the open reading frames (ORFs) suggest that, in addition to the much studied BARF0 ORF, there may be important products made from some of the upstream ORFs in the CST RNAs. Potential biological functions are identified for two of these. The product of the RPMS1 ORF is shown to be a nuclear protein that can bind to the CBF1 component of Notch signal transduction. RPMS1 can inhibit the transcription activation induced through CBF1 by NotchIC or EBNA-2. The protein product of another CST ORF, A73, is shown to be a cytoplasmic protein which can interact with the cell RACK1 protein. Since RACK1 modulates signaling from protein kinase C and Src tyrosine kinases, the results suggest a possible role for CST products in growth control, perhaps consistent with the abundant transcription of CST RNAs in cancers such as nasopharyngeal carcinoma.